Cardiovascular risk, quality of life and quality-adjusted years of life: a case report - Duque Henao, Sandra Lorena; Vásquez Velásquez, Johanna (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective: to determine the ratio cost-utility of cardiovascular diseases (CVD) promotion and prevention programs in a health care providing institution in the city of Medellin (Colombia). Methodology: the preventive program was compared before and after with the conventional control scheme under the design of a quasi experimental study evaluation with a non equivalent control group. Between the studied groups’ differences of the following results were evaluated at the end of the first and second year: Framingham score, direct cost of the program, quality of life, health indexes and quality-adjusted years of life. Results: in the evaluated groups a statistically meaningful difference was found between the initial and final moments for the variables: Framingham score, direct cost of the program, quality of life, health indexes and quality-adjusted years of life. Conclusion: the participation of patients in CVD prevention and promotion programs is related with risk reduction and a better quality of life.